Genotyping of HLA-class-I and II by PCR-SSP of Patients with Recurrent Aphthous Stomatitis - Al-Ghurabei, Batool H.; Saliah, Mustafa M.; Al-Hassan, Ahmed A .; Al-Nema, Ammra J.; Kadem, Ahmed (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Recurrent aphthous stomatitis is a common condition characterised by recurrent episodes of oral ulceration. Genetic factors have been implicated by numerous studies on the association of recurrent aphthous stomatitis and the genetically determined HLA subtypes.Objectives: Current study was established to shed light on the possible association of HLA class I and II alleles with recurrent aphthous stomatitis in Iraqi patients.Subjects and Methods: The study included 55 subjects: 30 recurrent aphthous stomatitis patients and 25 apparently healthy subjects as control. Polymerase chain reaction-specific sequence primers (PCR- SSP) assay was conducted to assess HLA- typing.Results: The present study showed a significant association of HLA-Cw*12:02:01-and HLADQB1* 02:01:01- alleles with recurrent aphthous stomatitis as compared with healthy control (P=0.041and P=0.028 respectively). Another interesting finding in this study was the significant low frequency of HLA-DQB1*05:01:01- allele in patients when compared with healthy control (P=0.036).Conclusion: These findings demonstrated that HLA-Cw*12:02:01- and HLA-DQB1*02:01:01-alleles may play a role in the etiology of the disease. Whereas HLA-DQB1*05:01:01-05 may confer protective effects against recurrent aphthous stomatitis.